Carbon Film Coating of Abutment Surfaces: Effect on the Abutment Screw Removal Torque - Corazza, Pedro Henrique [UNESP]; Silva, Alecsandro de Moura [UNESP]; Cavalcanti Queiroz, Jose Renato; Salazar Marocho, Susana Maria; Bottino, Marco Antonia [UNESP]; Massi, Marcos; Assuncao e Souza, Rodrigo Othavio de (Lippincott Williams & Wilkins, 2014)
Purpose: To evaluate the effect of diamond-like carbon (DLC) coating of prefabricated implant abutment on screw removal torque (RT) before and after mechanical cycling (MC).Materials and Methods: Fifty-four abutments for external-hex implants were divided among 6 groups (n = 9): S, straight abutment (control); SC, straight coated abutment; SCy, straight abutment and MC; SCCy, straight coated abutment and MC; ACy, angled abutment and MC; and ACCy, angled coated abutment and MC. The abutments were attached to the implants by a titanium screw. RT values were measured and registered. Data (in Newton centimeter) were analyzed with analysis of variance and Dunnet test (alpha = 0.05).Results: RT values were significantly affected by MC (P = 0.001) and the interaction between DLC coating and MC (P = 0.038). SCy and ACy showed the lowest RT values, statistically different from the control. The abutment coated groups had no statistical difference compared with the control. Scanning electron microscopy analysis showed DLC film with a thickness of 3 mm uniformly coating the hexagonal abutment.Conclusion: DLC film deposited on the abutment can be used as an alternative procedure to reduce abutment screw loosening.
Keywords: abutment; DLC; implant; plasma